Analysis of kinetic and diffusive data from the combustion of char pellets made with hybrid mixtures. (15th August 2019) - Marques, Edmundo; Ferreira, Tânia; Pereira, Carlos; Paiva, João Monney; Pinho, Carlos
Abstract: The presence of Cistus and Cytisus in Portugal is a potential source of an autochthonous renewable energy form. Portugal is also a main cork producer leading to large amounts of cork powders and residues, which can be incorporated in new fuel products. The present work studies the combustion of chars from hybrid pellets in a bubbling fluidized bed reactor. The hybrid pellets, made from blends of Cytisus with cork residues, Cistus with Eucalyptus and Cytisus with Cistus, were subsequently carbonized in nitrogen atmosphere at 800 °C, and later cut into smaller and more uniform particles with average lengths of 4.5, 7.5 and 11.5 mm approximately. Combustion tests were carried out at three different bed temperatures, 700, 800 and 900 °C. From the evolution of the overall combustion resistance of batches of these char pellets, kinetic and diffusive data were obtained. Contrary to the standard expected trend, a clear decrease of the overall combustion resistance with temperature increase, the results show that there are some unexpected approximations on the evolution of these overall combustion resistances. This is due to the influence of some ash components upon the combustion kinetics and that in some circumstances such influence overrides the standard temperature dependency. Highlights: Use of autochthonous Portuguese vegetable species for the production of biomass pellets. Determination of the combustion characteristics of chars made from hybrid biomass mixtures. Importance of alkali and alkali-earth elements in the ash for the control of the combustion kinetics.